Trajectory of Terminal Lucidity Phenomenon: Systematic Review - Novitasari, Yuni; Susanto, Eko; Mudaim, Mudaim (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
Terminal lucidity is a phenomenon characterized by the sudden reappearance of cognitive clarity in patients with severe cognitive impairment, such as dementia, near death. This systematic study aims to examine various aspects of the terminal lucidity phenomenon, from biological mechanisms, psychosocial impacts, to spiritual dimensions, especially through the lens of an Islamic perspective. The study was conducted using the Systematic Literature Review (SLR) approach according to the PRISMA guidelines, with an analysis of 82 open access articles from 2015 to 2024. The selection process included screening of titles, abstracts, and full texts, resulting in 40 articles that met the inclusion and exclusion criteria. The results of the analysis revealed that although biological mechanisms such as changes in neurotransmitters and brain electrical activity require further study, the terminal lucidity phenomenon has important implications for palliative care. This moment of clarity provides an opportunity for patients to communicate meaningfully and for families to say goodbye with hope. In addition to the medical aspect, terminal lucidity also reflects a significant spiritual dimension, where Islamic values interpret this phenomenon as divine intervention and a moment of final forgiveness. The findings of this study emphasize the need for a holistic approach that integrates emotional support, physical care, and spiritual guidance in end-of-life counseling. Further research is recommended to investigate the pharmacological mechanisms and the use of brain imaging technology to deepen the understanding of this phenomenon, so that the quality of patient care at the end of life can continue to be improved. This study makes an important contribution to expanding the multidisciplinary understanding of terminal lucidity and encourages the development of holistic palliative care guidelines, so that medical, psychosocial, and spiritual interventions can be optimized to accompany patients and their families to achieve a better quality of life.